A safflower oil based high‐fat/high‐sucrose diet modulates the gut microbiota and liver phospholipid profiles associated with early glucose intolerance in the absence of tissue inflammation. Issue 5 (22nd February 2017) - Danneskiold‐Samsøe, Niels Banhos; Andersen, Daniel; Radulescu, Ilinca Daria; Normann‐Hansen, Ann; Brejnrod, Asker; Kragh, Marie; Madsen, Tobias; Nielsen, Christian; Josefsen, Knud; Fretté, Xavier; Fjære, Even; Madsen, Lise; et al.
Abstract : Male C57Bl/6 mice were fed a linoleic acid‐rich high‐fat/high‐sucrose (HF/HS) diet based on safflower oil for 40 wk. Compared with mice fed a low‐fat/low‐sucrose diet, the HF/HS‐fed mice displayed a moderate weight gain with rapidly reduced glucose tolerance but sustained insulin sensitivity. The impaired glucose tolerance was accompanied by concurrent alterations in the hepatic phospholipid profile and changes in the composition of the gut microbiota. Abstract : Scope: Omega‐6 ( n ‐6) PUFA‐rich diets are generally considered obesogenic in rodents. Here, we examined how long‐term intake of a high‐fat/high‐sucrose (HF/HS) diet based on safflower oil affected metabolism, inflammation, and gut microbiota composition. Methods and results: We fed male C57BL/6J mice a HF/HS diet based on safflower oil—rich in n ‐6 PUFAs—or a low‐fat/low‐sucrose diet for 40 wk. Compared to the low‐fat/low‐sucrose diet, intake of the safflower‐based HF/HS diet only led to moderate weight gain, while glucose intolerance developed at week 5 prior to signs of inflammation, but concurrent with increased levels of linoleic acid and arachidonic acid in hepatic phospholipids. Intake of the HF/HS diet resulted in early changes in the gut microbiota, including an increased abundance of Blautia, while late changes coincided with altered inflammatory profiles and increased fasting plasma insulin. Analysis of immune cells in visceral fat and liver revealed no differences between diets before week 40, where the number of immune cells decreased in the liver of HF/HS‐fed mice. Conclusion: We suggest that a diet‐dependent increase in the n ‐6 to omega‐3 ( n ‐3) PUFA ratio in hepatic phospholipids together with gut microbiota changes contributed to early development of glucose intolerance without signs of inflammation.